Strategi Pengembangan Wisata Alam Camping Ground di Kabupaten Cianjur (Studi Kasus: Lembah Pasir Sumbul) - Fika Choirunnisa Suherman; Dewi Rahmi (Bandung Conference Series: Economics Studies, 2023)
Abstract. The purpose of this study was to determine the strengths, weaknesses, opportunities, threats and strategies for developing natural camping ground tourism. The research method used in this research is descriptive qualitative. Analysis of the data obtained from the results of interviews then make conclusions. The sample used was 7 people, with information from 4 visitors, 1 manager and 2 people from the surrounding community. The analytical method used is SWOT analysis to determine a strategy to be used as a camping ground tourism development strategy. The results showed that there were key factors from the camping ground in Lambah Pasir Sumbul indicating that there were 4 internal factors, 4 strengths and 4 weaknesses, external factors, 4 opportunities and 5 threats. SO Strategy, collaborating with investors for the development of tourist attractions, utilizing openness community and include them for the safety of tourist attractions. The WO strategy, helping to promote on various social media platforms by keeping up with technological developments, building and facilitating road accessibility for the convenience of visitors, Installing banners or banners on the main highway regarding the sand campsite. ST Strategy, Optimizing the natural potential that is owned by maintaining and carrying out maintenance of tourist attraction facilities, Organizing companion tourism objects so that the atmosphere at tourist objects is more varied. WT's strategy, increasing the government's role and support for tourism development, making attractive photo spots without damaging the surrounding environment and providing facilities for security such as evacuation routes Keywords: Camping Ground, Strategy, Development, Nature Tourism Abstrak. Tujuan penelitian ini untuk mengetahui kekuatan, kelemahan, peluang, ancaman serta strategi pengembangan wisata alam camping ground. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Analisis data diperoleh dari hasil wawancara, kemudian membuat kesimpulan. Sampel yang digunakan sebanyak 7 orang, dengan keterangan 4 orang pengunjung, 1 orang pengelola dan 2 orang masyarakat sekitar. Metode analisis yang digunakan adalah analisis SWOT untuk menentukan strategi untuk dijadikan strategi pengembangan wisata alam camping ground. Hasil penelitian menunjukan bahwa terdapat faktor kunci dari camping ground di Lambah Pasir Sumbul menunjukan ada 4 faktor internal, 4 kekuatan serta 4 faktor kelemahan terdapat faktor eksternal, 4 peluang dan 5 ancaman Strategi SO, melakukan kerjasama dengan pihak investor untuk pengembangan tempat wisata, memanfaatkan keterbukaan masyarakat dan mengikutsertakannya untuk keamanan tempat wisata. Strategi WO, membantu mempromosikan di berbagai platform sosial media dengan mengikuti perkembangan teknologi, membangun dan memfasilitasi aksesibilitas jalan untuk kenyamanan pengunjung, Memasang banner atau spanduk di jalan raya utama mengenai tempat camping pasir sumbul. Strategi ST, Mengoptimalkan potensi alam yang dimiliki dengan mempertahankan dan melakukan pemeliharaan terhadap fasilitas objek wisata, Mengadakan objek wisata pendamping agar suasana pada objek wisata lebih bervariasi. Strategi WT, meningkatkan peran dan dukungan pemerintah terhadap pengembangan pariwisata, membuat spot photo yang menarik tanpa merusak lingkungan sekitar dan menyediakan fasilitas untuk keamanan seperti jalur evakuasi. Kata kunci: Camping Ground, Strategi, Pengembangan, Wisata Alam.